2016
DOI: 10.5812/iranjradiol.31155
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Second Mesiobuccal Canals in Maxillary First Molars Using a New Angle of Cone Beam Computed Tomography

Abstract: BackgroundThe localization of the additional canal orifice is one of the primary factors influencing the success of endodontic treatment. To deal with this problem, several techniques that each have their own advantages and disadvantages have been discussed in the literature.ObjectivesThe aim of the present in vitro study was to review a new approach to localizing second mesiobuccal (MB2) canals in maxillary first molars using cone beam computed tomography (CBCT).Patients and MethodsThe CBCT scans of 296 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
1
2
1
Order By: Relevance
“…The second mesiobuccal canal (MB2) is one of the most commonly undetected canals in maxillary molars that escapes the pulp chamber at a critical mesial inclination, and consequently bends distally making the task difficult for dental practitioners [ 37 ]. The present study showed that the prevalence of an MB2 in maxillary first molars was 10 (8.1%), which was not in accordance with other CBCT research wherein the prevalence of an MB2 was reported at 36.3% [ 38 ], <50% [ 39 ] and 73.8% [ 40 ]. Furthermore, our result is contrary to a Micro-CT based study [ 41 ] which showed that MB2 was present in 80% of the first maxillary molar.…”
Section: Discussioncontrasting
confidence: 99%
“…The second mesiobuccal canal (MB2) is one of the most commonly undetected canals in maxillary molars that escapes the pulp chamber at a critical mesial inclination, and consequently bends distally making the task difficult for dental practitioners [ 37 ]. The present study showed that the prevalence of an MB2 in maxillary first molars was 10 (8.1%), which was not in accordance with other CBCT research wherein the prevalence of an MB2 was reported at 36.3% [ 38 ], <50% [ 39 ] and 73.8% [ 40 ]. Furthermore, our result is contrary to a Micro-CT based study [ 41 ] which showed that MB2 was present in 80% of the first maxillary molar.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the most frequently missed canals in maxillary molars is the second mesiobuccal canal with the canal exiting the chamber at an acute mesial inclination and subsequently bending distally which makes its negotiation a challenge for clinicians [26]. The present study showed that the prevalence of a second mesiobuccal canal in maxillary first molars was 36.3% which is in accordance with CBCT studies by Abd Latib et al [8] and Aktan et al [27] who reported a prevalence of below 50% in the Malaysian and Iranian populations, respectively. However, this finding is at a lower prevalence rate when compared to studies by Cleghorn et al [1], Choi et al [9] and Martins et al [28] which may be attributed to different sample sizes, methodologies and ethnic groups.…”
Section: Discussionsupporting
confidence: 89%
“…Two hundred sixty-one scans that met the inclusion and exclusion criteria were randomly selected, anonymized, and exported from the Abu Dhabi Health Authority database in Digital Imaging and Communication in Medicine (DICOM) format. The sample size of 261 scans was determined based on power analysis using Cochran's test, where the number of MB2 in previous studies [26,27] was considered the relevant difference.…”
Section: Sample Collectionmentioning
confidence: 99%